2019
DOI: 10.1002/er.4677
|View full text |Cite
|
Sign up to set email alerts
|

Energy‐efficient hybrid A/C and freshwater production system proposed for high latent load spaces

Abstract: Summary Huge amount of energies is consumed by the air conditioning (A/C) to maintain the required temperature and humidity inside spaces/applications of high humidly. An innovative A/C system that recovers the condenser heat in process air reheating and other useful thermal utilization is presented and investigated in this paper. For high coefficient of performance (COP) of the AC and more energy‐efficient system, the cold exhaust air rejected by the air condition system is also utilized to cool the condenser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In hybrid air conditioners, renewable energy is also used to minimize the rate of power consumption. Several researchers combined air conditioning and refrigeration systems with HDH water desalination systems in different configurations to obtain hybrid systems for cooling and air conditioning [9][10][11][12]. The effects of system configuration, operating conditions, and geometric parameters have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In hybrid air conditioners, renewable energy is also used to minimize the rate of power consumption. Several researchers combined air conditioning and refrigeration systems with HDH water desalination systems in different configurations to obtain hybrid systems for cooling and air conditioning [9][10][11][12]. The effects of system configuration, operating conditions, and geometric parameters have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that high portion of new energy access‐CCHP was more eco‐friendly and economical as compared to the conventional CCHP system. Furthermore, the researchers 38-40 have investigated the performance of various solar integrated multigenerational systems that were more efficient and environment‐friendly as compared to conventional stand‐alone systems.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the RH of air drops from 50.0% to 10.0% in the air heater and increased from 10.0% to 55.0% in the humidifier. Several researches combined the air conditioning and refrigeration systems with HDH water desalination systems in different configuration to obtain hybrid system for cooling and air conditioning systems 12‐16 . The effects of system configurations, the operating conditions and geometric parameters were investigated in these studies.…”
Section: Introductionmentioning
confidence: 99%